KEPATUHAN PERILAKU CUCI TANGAN TENAGA KESEHATAN PADA MASA PANDEMI COVID-19: A SYSTEMATIC REVIEW - Wahyuni Wahyuni; Meily Kurniawidjaja (Universitas Pahlawan, 2022)
Introduction: Health care handwashing behavior can significantly reduce health care-related infections (HAI) incIuding Covid-19. It is an effective, easier and cheaper step, but many factors affect it so that the compIiance of hand washing heaIth workers during the Covid-19 pandemic is stiII quite Iow. The purpose of this study is to anaIyze factors that affect the compIiance of handwashing heaIth workers during the Covid-19 pandemic. Method: This study is a systematic review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta AnaIyses) method using two articIe search engines nameIy Pubmed and Science Direct, using the keyword